Asymmetric Reciprocal Crossing Behavior of an Andean Blueberry (V. meridionale) × Lingonberry (V. vitis-idaea) Hybrid - Mark K. Ehlenfeldt; Elizabeth Ogden; Lisa J. Rowland (Plants, 2022)
The fertility and crossing behavior of a tetraploid hybrid of 4x Andean blueberry (V. meridionale) and lingonberry (V. vitis-idaea) was evaluated through a series of crosses. Crosses of the hybrid with highbush blueberry produced divergent results. When used as a female with V. corymbosum males, virtually all offspring were hexaploid, most likely arising from 2n = 4x = 48 female gametes, and 1n = 2x = 24 male gametes. However, when used as a male, tetraploid hybrids were produced, resulting from 1n = 2x = 24 gametes from each parent. To further examine this crossing behavior, the 4x V. meridionale—V. vitis-idaea interspecific hybrid was pollinated with 6x V. virgatum (rabbiteye blueberry). Analogous to the previous crosses, 7x hybrids were produced from the joining of 2n = 4x = 48 female gametes with 1n = 3x = 36 male gametes. Such reciprocal crossing asymmetry is unprecedented. The ability to produce both 6x and 4x offspring from the same V. corymbosum parents allows the potential of bridging a V. meridionale hybrid genotype to both the tetraploid (V. corymbosum) and hexaploid (V. virgatum) commercial crop levels.